P11: NEAR INFRARED FLUORESCENT CHOLANGIOGRAPHY IN LAPAROSCOPIC CHOLECYSTECTOMY: A SINGLE CENTRE FEASIBILITY STUDY. THE OPTIMUM DOSING REGIME, LIMITATIONS AND WHERE NEXT?. (27th April 2021) - Armstrong, G; Toogood, G; Jayne, DG; Smith, AM
Abstract: Introduction: This study explored near-infrared fluorescent cholangiography (NIRFC) with Indocyanine Green (ICG) during laparoscopic cholecystectomy (LC) surgery in a tertiary referral hepatobiliary unit. ICG binds to albumin and is excreted in bile. NIRFC utilises the fluorescent and excretory properties of ICG to provide dynamic extrahepatic bile duct mapping during LC. Method: Non-randomised single centre feasibility study. Twenty-two participants were sequentially allocated to four dosing subgroups prior to NIRFC assisted LC. Each received a single intravenous dose of ICG prior to LC with the Stryker Novadaq NIR laparoscope. The biliary anatomy was assessed with NIRFC at three time-points, detection was compared to radiological cholangiogram where available and surgeon satisfaction was assessed. Result: Eight participants received 2.5mg ICG 20-40min before surgery, four 0.25mg/kg 20-40min, five 90min – 180min and five 12 – 36 hour pre-operatively. Average age 50 years (S.D±15), BMI 27.5m 2  (S.D±3.6), 6/22 were acute LC procedures. The prolonged dosing interval produced increased extrahepatic biliary structure identification ( p = 0.016 ), reduced noise to signal ratio and was consistently preferred by the operating surgeon. NIRFC was inferior to radiological cholangiogram (n = 10) ( p = 0.014)  for bile duct mapping. We observed iatrogenic bile spillage saturating the field and obscuring structure differentiation and peri-hilar inflammation impeding fluorescent detection in acute LC. Conclusion: The dosing regimen 0.25mg/kg ICG 12 to 36 hours prior to surgery provides optimum NIRFC structure visualisation. Fluorescent tissue penetrance is limited in acute peri-hilar inflammation. More research in to the efficiency of NIRFC in emergency LC is required. Take-home message: An intravenous dose of 0.25mg/kg of Indocyanine Green 12 to 36 hours before surgery is the optimum dosing regimen for increased extra-hepatic bile duct structures with near infrared fluorescent cholangiography. The role of NIRFC in acute laparoscopic cholecystectomy surgery remains ill-defined.